Pengaruh Lama Pengasinan Terhadap Kadar Protein Putih Telur Itik - Siti Fatimah; Muji Rahayu; Siti Aminah (Journal of Health (JoH), 2014)
Background : Egg is one of the animal protein source, which has delicious taste, easy to digest and highly nutritious. Besides its affordable price, its supply availability is unquestionable as well. However, due to its short storability, it requires special treatment, such as preserving, to store it for long period. One way to preserve the egg is by pickling egg, which generally requires seven to ten days of marinating. During the process of marinating, there will be a visual change of egg white and yolk. Their structures will be more solid (the occurrence of thickening process) because salinization will lead to protein denaturalization. Consequently, it has an influence as well towards the content of egg white protein of duck egg. This study is aimed to explore the impact of various time of pickling egg towards egg white protein of duck egg. Method : The study where takes place in a laboratories, is a true experimental study for the reason that the researcher must provide intervention, hence all of potentially confounding variables are manageable. Samples that had been used in this study are duck eggs which were bought from North Brebes. This study is expected to generate data from four various time of pickling egg and control (no treatment). Since there are four samples, accordingly the number of data resulted are twenty. The resulted data will be descriptively presented in table, graph, presentation, and narration. Result : Protein level examination within duck white egg shows changes in protein levels that occurs in every variation of pickling egg time, where the average results of the assay of duck egg white protein is 14.94% without treatment (control), in five days of pickling time is 13.68%, in seven days of pickling time is 13.29%, in nine days of pickling time is 12.87% and eleven days of pickling time is 12.78%. Conclusion : There is a significant impact among the period of pickling time to the protein level degradation of duck white egg. Keywords : Duck egg, period of pickling time, level protein of duck white egg.